Narcissistic Personality Disorder and Berderline Personality Disorder in Terms of Self Psychology - Anli, Irem; Bahadir, Guler (Istanbul Univ, 2007)
This study aimed to compare the Narcissistic Personality Disorder (NPD) and the Borderline Personality Disorder (BPD) in terms of the development of narcissism on the basis of Self Psychology Approach. Thirty patients who were diagnosed as NPD, 30 patients who were diagnosed as BPD and 30 control subjects participated in the study. The basic research assumption was that the group diagnosed as NPD would be defensive in the grandiose self lure and the group diagnosed as BPD would be defensive in the idealized parental imago line according to Self Psychology. For this purpose both of the groups were given the Self Psychology Inventory, which had been then assessed by using the SCID-II. According to the results the BPD group was found to be defensive in idealized parental imago line and NPD group was found to be defensive in both grandiose self and idealized parental imago lines.
Keywords: Narcissism; Narcissistic Personality Disorder; Borderline Personality Disorder; Kohul; Self Psychology; Kernberg